2016
DOI: 10.3389/fped.2016.00139
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Bacterial Colonization in the First 2 Weeks of Life of Nigerian Neonates Using Standard Culture Methods

Abstract: ObjectiveThe pattern and timing of development of intestinal microflora in Nigerian infants have been scarcely researched. This study was carried out to investigate the bacteria flora in the rectum of healthy neonates in Ibadan, Nigeria.Patients and methodsIn this hospital-based longitudinal study, rectal swabs of 70 neonates were taken within 6–12 h of birth (day 1) and subsequently on days 3, 9, and 14. Information collected included maternal sociodemographic characteristics, antibiotic use for the neonates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
(44 reference statements)
2
10
0
Order By: Relevance
“…Intestinal microecology is the most complex microecosystem in the human body. It not only is involved in the digestion of food, the absorption of nutrients, and the synthesis of vitamins but also plays an important role in immune regulation ( 16 ). Gut microbiota dysbiosis is closely associated with localized gastroenterologic disorders ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal microecology is the most complex microecosystem in the human body. It not only is involved in the digestion of food, the absorption of nutrients, and the synthesis of vitamins but also plays an important role in immune regulation ( 16 ). Gut microbiota dysbiosis is closely associated with localized gastroenterologic disorders ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly in a study of 65-70 Nigerian neonates, rectal swabbed samples consisted mainly of coagulase-negative Staphylococcus (38.6%), followed by S. aureus (31.4%) and E. coli (30%) on the first day of life. 122 Coagulase-negative Staphylococcus remained the most frequently isolated bacteria at d 3, 9 and 14 d postpartum. Interestingly, this study reported an absence of Actinobacteria such as Bifidobacteria spp., which is consistent with previous findings in Nigeria published in 1982.…”
Section: Hygiene Practices Impact the Ecological Succession Of Bactermentioning
confidence: 91%
“…136 Moreover, despite high relative abundances, several papers still report low prevalence (<60% colonized) including papers from Belgium (57%), 137 Greece (35%), 21 Ireland (47%) 101 the United Kingdom (21%), 129 the United States (none detected [ND]), 138 Ethiopia (35%) 105 and Nigeria (ND). 122 While these studies show that Bifidobacteria spp. are often only present in a small fraction of infants or are not numerically dominant, some argue that the paucity of Bifidobacteria spp.…”
Section: Ecological Succession Of Bifidobacteria Sppmentioning
confidence: 97%
See 2 more Smart Citations